2016
DOI: 10.11152/mu.2013.2066.181.ich
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of EUS elastography followed by contrast-enhanced EUS in patients with focal pancreatic masses and negative EUS-guided FNA

Abstract: Aim: It is well known that endoscopic ultrasound guided fine needle aspiration (EUS-FNA) has a high sensitivity (over 85%) and specificity (100%) for diagnosis of pancreatic cancer. The aim of the study was to establish a EUS based clinical diagnostic algorithm in patients with pancreatic masses and negative cytopathology after EUS-FNA, based on previously published results and cut-offs of real-time elastographic (RTE) EUS and contrast-enhanced harmonic (CEH) EUS. Material and methods: We included in the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 27 publications
0
33
0
1
Order By: Relevance
“…Their cut-off values were decided by using previous published studies, or the one with the highest accuracy rate based on the receiver operator characteristic (ROC) curves. Four studies also evaluated CE-EUS [4,19,20,22], and 4 studies evaluated EUS-FNA [7,8,19,22].…”
Section: Search Results and Characteristics Of The Selected Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Their cut-off values were decided by using previous published studies, or the one with the highest accuracy rate based on the receiver operator characteristic (ROC) curves. Four studies also evaluated CE-EUS [4,19,20,22], and 4 studies evaluated EUS-FNA [7,8,19,22].…”
Section: Search Results and Characteristics Of The Selected Studiesmentioning
confidence: 99%
“…Characteristics of the selected studies are shown in Table I. Six studies used SH as the diagnostic standard [4,9,22,[26][27][28], 7 studies used SR [7][8][9]16,19,23,27,30], 3 studies used color pattern [20,23,24],and 3 studies used elastic score [21,25,29]. For those using SH, the cut-off values ranged from 62 to 80, and for those using SR, the cut-off values varied from 3.05 to 24.82.…”
Section: Search Results and Characteristics Of The Selected Studiesmentioning
confidence: 99%
See 3 more Smart Citations